Acupuncture for the treatment of thalamencephalic and mesencephalic injury secondary to electrical trauma: A case report - Jiang, Hailun; Zhang, Yi; Zhang, Jieying; Li, Boxuan; Zhu, Weiming; Liu, Chaoda; Deng, Shizhe; Du, Yuzheng; Meng, Zhihong (Frontiers in Neuroscience, 2023)
In a case of thalamencephalic and mesencephalic injury secondary to electrical trauma, a 29-year-old patient has been receiving manual acupuncture for 17 months in National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion. As a result of treatment, the patient's self-care ability and quality of life have greatly improved. In order to fully understand how acupuncture can benefit neurological sequelae resulting from electrical trauma, further research is needed. Additionally, there should be consideration given to the promotion of acupuncture therapy in the neurological sequelae of electric shock.